Pharmacological Properties of Genista sagittalis L. (Fabaceae) Grown in Turkey - Pelin Şenel; Bleda Can Sadıkoğulları; Elif Çepni Yüzbaşıoğlu; Gülnur Mertoğlu Elmas; Dilek Oral; Ayşegül Gölcü; Ayşe Daut Özdemir (Indonesian Journal of Chemistry, 2023)
The genus Genista L. (Family: Fabaceae) is a plant having several traditional uses for treating common ailments such as diabetes, ulcer, and respiratory diseases. In this current study, the composition of essential oil and the biological activities of Genista sagittalis L. (Fabaceae) from Kocaeli: Yuvacık Dam Basin have been studied. A total of fourteen components were identified in the essential oil. The identified compounds belonged to straight-chain alkane, aromatic ether, and terpenoid derivatives. The antibacterial activity analyses demonstrated that G. sagittalis flower extract only had low activity against P. mirabilis and P. aeruginosa with MICs 1 to 2 mg/mL, as the peduncle extract showed strong anti-QS activity at 1.3 mg/mL. To the best of our knowledge, the current work is the first to report the antimicrobial and anti-quorum sensing activity of G. sagittalis growing in Turkey. Double-stranded DNA binding affinity investigations of the flower and peduncle ethanol extracts indicate that there are interactions with double-stranded DNA and related binding constants (Kb) were found as 1.97×103±0.37 and 3.68×102±0.44 for the flower and peduncle extract, respectively.